Management of complications by uniportal video-assisted thoracoscopic surgery - Fernández Prado, Ricardo; Fieira Costa, Eva; Delgado Roel, María; Fernández, Lucía Méndez; Paradela de la Morena, Marina; de la Torre, Mercedes; Gonzalez-Rivas, Diego (Journal of thoracic disease, 2014)
Since the video-assisted thoracoscopic surgery (VATS) anatomic lobectomy for lung cancer was described two decades ago, many units have successfully adopted this technique. VATS lobectomy is a safe and effective approach for the treatment not only of early stage lung cancer but also for more advanced disease. It represents a technical challenge. As the surgeon's experience grows, more complex or advanced cases are approached using the VATS approach. However, as VATS lobectomy has been applied to more advanced cases, the rate of conversion to open thoracotomy has increased, particularly early in the surgeon's learning curve, mostly due to the occurrence of complications. The best strategy for facing complications of VATS lobectomy is to prevent them from happening. Avoiding complications is subject to an appropriate preoperative workup and patient selection. Planning for a VATS resection as safely as possible involves the consideration of the patient´s characteristics and the anticipated technical aspects of the case. Awareness of the possibility of intraoperative complications of VATS lobectomy is mandatory to avoid them, and the development of management strategies is necessary to limit morbidity if they occur.